Handbook of Industrial Crystallization. Third edition. Edited by Allan S. Myerson, Deniz Erdemir and Alfred Y. Lee. Cambridge University Press, 2019. Pp. 538. Price GBP 145 (hardcover). ISBN 9780521196185. Issue 3 (14th April 2020) - Benz, Klaus-Werner
Abstract : Book review Abstract : Book review